Laboratory and match physiological data from an elite male collegiate soccer athlete - Sapp, R. M.; Aronhalt, L.; Landers-Ramos, R. Q.; Spangenburg, E. E.; Wang, M. Q.; Hagberg, J. M. (The Journal of Strength and Conditioning Research, 2017)
This study compared physiological data from an elite collegiate soccer player to those of his teammates over 2 seasons. The player of special interest (player A) was the winner of the MAC Hermann Trophy and was therefore considered the top player in National Collegiate Athletic Association (NCAA) division I soccer for each of the 2 seasons in which data were collected. Maximal oxygen consumption (VO2max) was measured during preseasons and heart rate (HR) was recorded during competitive matches. Polar Training Loads (PTL) were calculated using the Polar Team2 Pro (Polar USA) system based on time spent in HR zones. Player A had a lower VO2max than the team average in 2012 (56 vs. 61.5 ± 4.3 ml/kg/min) and a similar value in 2013 (54 vs. 56.9 ± 5.1 ml/kg/min). During matches, player A showed consistent significant differences from the team in percentage of time spent at 70-79% maximal heart rate (HRmax) (12.8 ± 5.5% vs. 10.1 ± 4.0%), 80-89% HRmax (54.3 ± 11.5% vs. 29.3 ± 6.8%), and 90-100% HRmax (23.1 ± 10.6% vs. 45.4 ± 8.5%). This led to a consistently lower PTL per minute accumulated by player A compared with his teammates (3.6 ± 0.4 vs. 4.4 ± 0.3), which may be beneficial over a season and may be related to his success. Thus, the ability to regulate moments of maximal exertion is useful in reducing training load and may be a characteristic of elite players, although whether our findings relate to differences in the playing style, position, or aerobic capacity of player A are unknown.